Implementasi Metode Analytical Hierarchy Process dengan Weighted Product untuk Rekomendasi Penentuan Pegawai Terbaik berdasarkan Kinerja (Studi Kasus Divisi CCRD Bank BTN Kantor Pusat Jakarta) - Irvan Windy Prastyo; Nurul Hidayat; Tibyani Tibyani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Employee performance is a factor that influences the results to be achieved by a company. The effort are made to achieve the target of the Bank Tabungan Negara (BTN) Consumer Collection & Remedial Division (CCRD) division on employee performance is to assess employee performance. This study aims to apply the algorithm Analytic Hierarchy Process with Weighted Product method, and test the accuracy of recommendations for determining the best employee of the BTN CCRD division. The basic method used in this research is the AHP-WP method. The Analytic Hierarchy Process (AHP) method in this study will be used for weighting criteria and followed by the Weighted Product (WP) method to calculate the alternative value of each of the criteria and provide a sequence of recommendations for employees. This system uses 60 data which form the basis of calculations with 10 test data in each position with as many as 6 positions, namely ST, STC, AFC, TLFC, CS, and BC. The application of the AHP-WP method is to determine the recommendations of the best employees of the BTN bank by using assessment criteria such as shifting, damming, restructuring, ICOLL input, assessment 1, assessment 2 and assessment 3, and each position has different criteria. The results of this study indicate that the design of employee recommendation systems using the Analytic Hierarchy Process with Weighted Product method with the system java programming language running well, with the results in accordance with the manualization calculation and obtained the highest correlation closeness which is 1, which means perfect correlation and the lowest 0.5, which means a quite thightly correlation with each of the 5 top ranking and 5 lastly data in testing.